Factors affecting job-site productivity of construction workers in lagos state - Jimoh, R.A.; Ijigah, A.E.; Elegbede, I. (Penerbit UKM, 2013)
Productivity is one of the most important factors affecting the overall performance of any organisation whether large or small organisation. It is on the basis of this that the study assess the factors that affect job-site productivity in Lagos State with consideration on recruitment policy, types of training and factors that affect quality of workers and their contribution to the various organisations surveyed. This is done through the self administration of 100 structured questionnaires to elicit information from the respondents using convenience sampling method. The results showed that 64.7% of the respondents used on the job training for their workers and 54.3% of the respondents conduct training for their staff as required. Experience of workers was ranked 1st while age of workers was ranked 14th out of 16 factors. Furthermore, improvements are needed in the areas of developing people (42%), safety consciousness (34%) and planning effectiveness (26%). It is however suggested among others that efforts should be made by the firms to invest in developing its work force (ability to select, train and appraise personnel, set standard of performance) so that on the long run, this will yield positive improvement on the overall productivity.